PENATALAKSANAAN FISIOTERAPI PADA KASUS FROZEN SHOULDER DEKSTRA DENGAN MODALITAS ULTRASOUND DIATHERMY DAN CODMAN PENDULUM EXERCISE DI RSUD CIBABAT KOTA CIMAHI - Shelly Novianti Ismanda; Arif Rustiana (INFOKES (Informasi Kesehatan), 2021)
ABSTRACT This research aims to review physiotherapy management in case of frozen shoulder dextra with modalities ultrasound diathermy (us) and codman pendulum exercise. The research methods that were used is qualitative research methods with data accumulation techniques in the form of interview and inspection health status. This research was conducted in the Physiotherapy Unit with 1 person sample, namely frozen shoulder dextra patient who visited RSUD Cibabat Cimahi at the research time. The results research showed developments with ultrasound diathermy (us) which helped reduce pain and codman pendulum exercise which helped increase range of motion and muscle strength. After 6 time therapy, obtained the result of a decrease in motionless pain shoulder dextra T1 (1,4) to T6 (0), press pain T1 (2,3) to T6 (0), motion pain T1 (5,7) to T6 (1,3). The increase active range of motion shoulder dextra flexion T1 (147º) to T6 (180º), extension T1 (34º) to T6 (45º), endorotation T1 (83º) to T6 (90º), exorotation T1 (45º) to T6 (60º), abduction T1 (157º) to T6 (177º), adduction T1 (33º) to T6 (45º). The increase of muscle strength shoulder dextra flexion T1 (3) to T6 (5), extension T1 (3) to T6 (4), endorotation T1 (3) to T6 (5), exorotation T1 (4) to T6 (5), abduction T1 (2) to T6 (5), adduction T1 (2) to T6 (4). For optimize result therapy patient are advised to reduce activities of carrying heavy burden that focuses on the right shoulder.